2020
DOI: 10.3389/fped.2020.00318
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Lung Health Trajectories for Survivors of Preterm Birth

Abstract: Rates of preterm birth (<37 weeks of gestation) are increasing worldwide. Improved perinatal care has markedly increased survival of very (<32 weeks gestation) and extremely (<28 weeks gestation) preterm infants, however, long term respiratory sequalae are common among survivors. Importantly, individual's lung function trajectories are determined early in life and tend to track over the life course. Preterm infants are impacted by antenatal, postnatal and early life perturbations to normal lung growth and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 140 publications
0
12
0
Order By: Relevance
“…160 The fixed and reversible component to airway hyper-reactivity in preterm infants may be more pronounced in those with BPD, as noted by consistently reduced spirometry values. 49 A systematic review and meta-analysis measuring bronchial hyper-responsiveness (BHR) in adults and children born preterm with and without BPD revealed that the risk of BHR was increased in participants with BPD for both methacholine challenge (OR 2.59, 95% CI, 1.50 to 4.50) and exercise challenge (OR 5.13, 95% CI, 1.82 to 14.47). To date there is no evidence linking inhaled steroids and bronchodilators with either reduction in BPD or mortality.…”
Section: Inhaled Bronchodilatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…160 The fixed and reversible component to airway hyper-reactivity in preterm infants may be more pronounced in those with BPD, as noted by consistently reduced spirometry values. 49 A systematic review and meta-analysis measuring bronchial hyper-responsiveness (BHR) in adults and children born preterm with and without BPD revealed that the risk of BHR was increased in participants with BPD for both methacholine challenge (OR 2.59, 95% CI, 1.50 to 4.50) and exercise challenge (OR 5.13, 95% CI, 1.82 to 14.47). To date there is no evidence linking inhaled steroids and bronchodilators with either reduction in BPD or mortality.…”
Section: Inhaled Bronchodilatorsmentioning
confidence: 99%
“…Pulmonary function testing has been proposed to gain meaningful information in the diagnosis of BPD and validation of proposed definitions 4950. Preterm birth and very low birth weight (VLBW) status have been consistently associated with diminished lung capacity,515253 increased airway obstruction,51525354 impaired gas exchange,51 and a premature decline in respiratory function 5354.…”
Section: Physiological Measurements In the Diagnosis Of Bpdmentioning
confidence: 99%
“…The prevalence of premature birth (<37 weeks gestation) is ~10% worldwide [70] and increasing [71], while improvements in perinatal care mean survival rates for very (<32 weeks gestation) and extremely (<28 weeks gestation) preterm infants are also increasing [71]. Consequently, longterm respiratory morbidity as a result of prematurity is also rising [72].…”
Section: Prematurity/chronic Lung Diseasementioning
confidence: 99%
“…Although perinatal care improvement has promoted premature infants' survival, long‐term respiratory morbidity remains a critical complication of preterm birth, 1 in particular, the increasing rate of bronchopulmonary dysplasia (BPD) 2 . However, the altered lung function seems associated not only with BPD diagnosis but primarily with preterm birth 3,4 .…”
Section: Introductionmentioning
confidence: 99%